Character-Based Knowledge Construction in Personal Bankers Within Banking Service Practices - David Christian Engelbert Lisapaly; La Ode Hamida; Rince Tambunan; Titien Rahayuningsih (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to analyze the construction of character-based knowledge among personal bankers as bank marketing personnel in banking service practices. It explores how knowledge is developed and internalized through work experience, customer interactions, and organizational culture to enhance service quality. Design/methodology/approach – This study adopts a qualitative approach with a descriptive-interpretative design. Data were collected through in-depth interviews and observations involving purposively selected personal bankers at a commercial bank branch in Kendari City, Southeast Sulawesi. The data were analyzed using thematic analysis. Findings – The findings reveal that personal bankers’ knowledge is constructed through professional experience, customer interactions, and organizational culture. This knowledge is internalized into character values, including integrity, empathy, and responsibility, which are reflected in customer-oriented and communicative service behaviors. However, the consistent application of these values is constrained by performance target pressures. Originality/Value – This study highlights the importance of character-based knowledge as a foundation for improving banking service quality. It contributes to the literature on human resource development and organizational behavior by demonstrating the need for organizational support and continuous learning to strengthen the internalization of character values in banking service practices.